Perbandingan Metode Weighted Moving Average dan Single Exponential Smoothing Angka Partisipasi Sekolah Wilayah Adat, Papua - Felix Reba; Alvian Sroyer; Sara Yokhu; Agustinus Langowuyo (Universitas PGRI Palembang, 2021)
School Participation Rate (SPR), which is one of the indicators of successful education, includes the development or improvement of educational services in regions of Indonesia. Regarding the extent of each customary territory of Papua Province, there are very significant differences in SPR in the last 10 years, especially in 2010-2019. Some districts have experienced a drastic decline in their SPR in the last 4 years and some have fluctuating data. This study aims to compare the Weighted Moving Average (WMA) and Single Exponential Smoothing (SES) methods on SPR data at the elementary, junior high, senior high schools and equivalent levels in five customary territory of Papua Province. This study uses data on the percentage of SPR in 2010-2019 taken from the Central Statistics Agency (BPS) of Papua Province. Based on the results of Mean Absolute Percentage Error (MAPE), SES method is better than WMA. It means that the SES method is a suitable method for forecasting fluctuating SPR data. Thus, SES can be a reference method for the government for forecasting SPR in the coming year. If researchers use more data and more complex variables, it will require additional applications such as Matlab and POM QM.